ナンキョク ライト タニ ニ オケル エンルイ ノ キゲン - 富山, 千里; トミヤマ, チサト; 北野, 康; キタノ, ヤスシ; Tomiyama, Chisato; Kitano, Yasushi (1985)
P(論文) 南極, 上部ライト谷における塩類の分布および硫黄の安定同位体組成を調べた。ドンファン湖盆における塩収支の計算から, ドンファン池の塩化カルシウム型の塩類の起源は, 主として塩化カルシウム型の地下水であり, また, 硫酸イオンとカルシウムイオンの起源については, 地下水と融氷水以外の供給源, たとえば風送塩として運ばれてくる硫酸塩などを考慮に入れなくてはならないことが明らかとなった。この塩収支の計算から, ドンファン池の年齢は, 9000-37000年より新しいことが示唆された。硫黄の同位体比からは, ラビリンス地域とドンファン湖盆の硫酸イオンの起源を明らかにすることはできなかった。バンダ湖盆の硫酸イオンについては, かつて谷がフィヨルドとなった時に残された海水起源の硫酸塩が寄与していると推察された。 Salt distribution and stable isotope composition of sulfur have been investigated in the upper Wright Valley area, Antarctica. From the discussion on the mass balance of chemical constituents in the Don Juan basin, it is clear that calcium chloride-rich groundwater is an important source for the pond water, and another sources of sulfate and calcium ions other than groundwater and stream water should be considered. The age of Don Juan Pond was calculated to be younger than 9000-37000 years. The isotope composition of sulfur does not indicate the origin of sulfate ions at the Labyrinth area and the Don Juan basin. For the Vanda basin, it is supposed that the sulfate origin is sulfate minerals which were formed from seawater on the slope of the valley during the valley was fjord. departmental bulletin paper